1998
DOI: 10.1108/09600039810234924
|View full text |Cite
|
Sign up to set email alerts
|

Genetic algorithms in the design of complex distribution networks

Abstract: Reviews the value of network concepts as a means of portraying complex logistics and distribution systems. Reports on research which focuses on the broader issues of model formulation and solution techniques rather than specific applications. Addresses the issues of designing networks with a tree structure, and also more general ones in which loops are allowed and redundancy enforced. The decision variables involved are related to whether or not a link should exist between two specific pairs of nodes, and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Simplicity of operation and power of effect are two of the main attractions of the GA approach (Goldberg, 1989). Berry et al (1998) described the application of GA in the design of complex distribution networks to decide the node-link topology and showed that the combined use of GA and linear or non-linear programming is an effective approach to solve network design problems. Disney et al (1997) demonstrated the use of a model of a decision support system coupled with a simulation facility; a GA optimisation procedure can yield enhanced performance to the production control function.…”
Section: Proposed Genetic Algorithmsmentioning
confidence: 99%
“…Simplicity of operation and power of effect are two of the main attractions of the GA approach (Goldberg, 1989). Berry et al (1998) described the application of GA in the design of complex distribution networks to decide the node-link topology and showed that the combined use of GA and linear or non-linear programming is an effective approach to solve network design problems. Disney et al (1997) demonstrated the use of a model of a decision support system coupled with a simulation facility; a GA optimisation procedure can yield enhanced performance to the production control function.…”
Section: Proposed Genetic Algorithmsmentioning
confidence: 99%
“…There is little information on how these ideas can be realized into a set of tools that could help managers of SMEs overcome the complexities of dealing with collaborative planning efforts. Even the little information that is available for realizing tools for collaborative planning either use complex techniques such as genetic algorithm (Berry et al, 1998), artificial intelligence (McMullen, 2001), stochastic programming (MirHassani, 2000), statistical analysis (Reutterer and Kotzab, 1999) that require mathematicians or specialists for using it, or demands very expensive and time consuming installation of third party implementation.…”
Section: Literature Reviewand the Problem Statementmentioning
confidence: 99%
“…In addition, increased attention has been given to evolutionary concepts in economic change (Nelson and Winter, 1982), game theory (Smith, 1982), new product growth (Tellis and Crawford, 1981), and breeding competitive strategies (Midgley et al, 1997). Furthermore, genetic algorithms (GAs) have been used to model new product development and design processes (Balakrishnan and Varghese, 1996;Natter et al, 2001), strategic groups (Lee et al, 2002), retail inventory and space allocation (Urban, 1998), retail site selection (Hurley et al, 1995), and the design of distribution networks (Berry et al, 1998). Recently, there have been attempts to breed artificial agents to model economic and marketing phenomena (Arthur, 1991;Holland and Miller, 1991;Midgley et al, 1997).…”
Section: Introductionmentioning
confidence: 99%